Imagens da Marie Claire francesa: resiliência feminina durante a Segunda Guerra Mundial - Miranda, Atena Pontes de (2021)
Between 1939 and 1944, that is, in the middle of the Second World War, the Marie Claire Magazine was published in France, this one had as context the female daily life according to the reality of the belligerent time. This investigation has as main objective to analyze in the original editions of Marie Claire (1939-1944) records that show the resilience of French women in that period and the process of educational mediation in the Exhibition Pour vous, Mesdames! La mode en temps de Guerre, held in Lyon, France. Through bibliographic analysis, a qualitative research was made using the “structure of Atlas Mnemosyne”, together with the concepts of Nachleben and Engram proposed by Warburg in an “operational understanding of images in an anachronistic view” by Didi-Huberman with Abordagem Triangular of Ana Mae Barbosa. The methodology used is based on the analysis of images from the women's magazine Marie Claire from Eveline Sullerot and Alexie Geers, the concept of social image of women according to Simone de Beauvoir and Fashion at War from Dominique Veillon. Hence, a reflection on the question of the resilience of French women in World War II from the perspective of a social memory, of the research object and of the museum space is presented.